GENDER TYPING PADA PRODUK TEKNOLOGI DALAM KOMUNITAS ONLINE - Kania, Dessy; Faruk, Faruk; Budiawan, Budiawan (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2017)
The growing usage of technological products such as smartphones has an evitable consequence in social practices in terms of smartphone consumptions. These practices are not only related to class construction and social status, but also identity struggles in terms of gender construction particulary in one of the Apple’s largest online communities on Instagram; @idevice.indonesia. Using cultural studies approach, this paper exposes the meanings behind the practice of gender typing towards iPhone products within the @idevice.indonesia community. Gender typing is a process in which a person associates him/herself with a particular gender and then behaves accordingly to the values ​and the attributes adopted with the particular sex that they identify as his/hers. From this analysis an insightful picture was produced regarding the meanings behind the practice of gender typing towards product technology in Indonesia that can provide critical inspiration for consumers as well as contribution for technology producers.